Urine ALCAM, PF4 and VCAM-1 Surpass Conventional Metrics in Identifying Nephritis Disease Activity in Childhood-Onset Systemic Lupus Erythematosus - Soliman, Samar A.; Haque, Anam; Vanarsa, Kamala; Zhang, Ting; Ismail, Faten; Lee, Kyung Hyun; Pedroza, Claudia; Greenbaum, Larry A.; Mason, Sherene; Hicks, M. John; Wenderfer, Scott E.; Mohan, Chandra (Frontiers in Immunology, 2022)
Objectives: Serial kidney biopsy for repeat evaluation and monitoring of lupus nephritis (LN) in childhood-onset systemic lupus erythematosus (cSLE) is challenging, thus non-invasive biomarkers are needed. Here, we evaluate the performance of ten urine protein markers of diverse nature including cytokines, chemokines, and adhesion molecules in distinguishing disease activity in cSLE. Methods: Eighty-four consecutive pediatric patients fulfilling ≥4 ACR criteria for SLE and twenty-five healthy controls were prospectively recruited for urine testing of 10 protein markers normalized to urine creatinine, namely ALCAM, cystatin-C, hemopexin, KIM-1, MCP-1, NGAL, PF-4, Timp-1, TWEAK, and VCAM-1 by ELISA. Samples from patients with active LN and active non-renal SLE were obtained prior to onset/escalation of immunosuppression. SLE disease activity was assessed using SLEDAI-2000. Fifty-nine patients had clinically active SLE (SLEDAI score ≥4 or having a flare), of whom 29 patients (34.5%) were categorized as active renal (group L+N+), and 30 patients (35.7%) were active non-renal (group L+N-). Results: Urine concentrations of ALCAM, KIM-1, PF4 and VCAM-1 were significantly higher in active LN patients compared to active non-renal SLE, inactive SLE and healthy controls. Five urine proteins differed significantly between 2 (hemopexin, NGAL, MCP1) or 3 (Cystatin-C, TWEAK) groups only, with the highest levels detected in active LN patients. Urine ALCAM, VCAM-1, PF4 and hemopexin correlated best with total SLEDAI as well as renal-SLEDAI scores (p < 0.05). Urine ALCAM, VCAM-1 and hemopexin outperformed conventional laboratory measures (anti-dsDNA, complement C3 and C4) in identifying concurrent SLE disease activity among patients (AUCs 0.75, 0.81, 0.81 respectively), while urine ALCAM, VCAM-1 and PF4 were the best discriminators of renal disease activity in cSLE (AUCs 0.83, 0.88, 0.78 respectively), surpassing conventional biomarkers including proteinuria. Unsupervised Bayesian network analysis based on conditional probabilities re-affirmed urine ALCAM as being most predictive of active LN in cSLE patients. Conclusion: Urinary ALCAM, PF4, and VCAM-1 are potential biomarkers for predicting kidney disease activity in cSLE and hold potential as surrogate markers of nephritis flares and prognosis in these patients.